Accounting Conservatism and Stock Price Crash Risk: Firm‐level Evidence - Kim, Jeong‐Bon; Zhang, Liandong (Contemporary Accounting Research, 2016)
Abstract Using a large sample of U.S. firms during 1964–2007, we find that conditional conservatism is associated with a lower likelihood of a firm's future stock price crashes. This finding holds for multiple measures of conditional conservatism and crash risk and is robust to controlling for other known determinants of crash risk and firm‐fixed effects. Moreover, we find that the relation between conservatism and crash risk is more pronounced for firms with higher information asymmetry. Overall, our results are consistent with the notion that conditional conservatism limits managers’ incentive and ability to overstate performance and hide bad news from investors, which, in turn, reduces stock price crash risk.